معالجة القضايا الأسرية في الجزائر من خلال النوازل الفقهية خلال العهد العثماني1518/1830(الونشريسي نموذجا) - سارة حافي راسو; سرور يوسفي (My University, 2023)
Abstract: The family in the city of Algiers during the Ottoman era occupied animportant aspect of social life because it is the basis of any society, and therehave been many sources that dealt with family topics, including jurisprudentialcalamities that do not belong in terms of classification of science to thehistorical field, but they include important historical texts, filling the gaps left bytraditional historical sources and documents in family topics in particular, andthis science has many scholars and jurists who were interested in authorship andclassification in it from Among them is the jurist Ahmed bin Yahya Al-Wancharisi, who died in the 15th century AD, and his most famousclassification in this field is "the Arabized standard", he has been interested in itfrom the beginning of formation (marriage), cohesion and harmony to thedifferences and disputes that occur within the family. ------------------------------------------------------------------- الملخص: احتلت الأسرة في مدينة الجزائر خلال العهد العثماني جانبا مهما من جوانب الحياة الاجتماعية لأنها أساس أي مجتمع، وكانت هناك العديد من المصادر التي تناولت مواضيع الأسرة، ومنها النوازل الفقهية التي لا تنتمي من حيث تصنيف العلم إلى الحقل التاريخي، بل تتضمن نصوصا تاريخية مهمة، سد الثغرات التي خلفتها المصادر والوثائق التاريخية التقليدية في موضوعات الأسرة على وجه الخصوص، ولهذه العلوم العديد من العلماء والفقهاء الذين اهتموا بالتأليف والتصنيف فيها من بينهم الفقيه أحمد بن يحيى الونشريسي المتوفى في القرن 15م، وأشهر تصنيفاته في هذا المجال هو "المعيار المعرب "، لقد اهتم بها منذ بداية التكوين (الزواج) والتماسك والتلاحم و الانسجام وصولا الى الاختلافات والنزاعات التي تحدث داخل الأسرة. --------------------------------------------------------------- -Résumé : La famille dans la ville d’Alger à l’époque ottomane occupait un aspect important de la vie sociale parce qu’elle est la base de toute société, et il y a eu de nombreuses sources qui ont traité de sujets familiaux, y compris les calamités jurisprudentielles qui n’appartiennent pas en termes de classification de la science au domaine historique, mais qui comprennent des textes historiques importants, combler les lacunes laissées par les sources et les documents historiques traditionnels dans les sujets familiaux en particulier, et cette science a de nombreux érudits et juristes qui étaient intéressés par la paternité et la classification parmi eux est le juriste Ahmed bin Yahya Al-Wancharisi, qui est mort au 15ème siècle après JC, et sa classification la plus célèbre dans ce domaine est « la norme arabisée », Il s’y est intéressé depuis le début de la formation (mariage), de la cohésion et de l’harmonie jusqu’aux différences et aux disputes qui se produisent au sein de la famille.